2018
DOI: 10.3390/ijms19082229
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Expression of a Thellungiella salsuginea Aquaporin Gene, TsPIP1;1, Increased the Salt Tolerance of Rice

Abstract: Aquaporins play important regulatory roles in the transport of water and small molecules in plants. In this study, a Thellungiella salsuginea TsPIP1;1 aquaporin was transformed into Kitaake rice, and three transgenic lines were evaluated by profiling the changes of the physiological metabolism, osmotic potential, and differentially expressed genes under salt stress. The TsPIP1;1 protein contains six transmembrane domains and is localized in the cytoplasm membrane. Overexpression of the TsPIP1;1 gene not only i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 47 publications
4
19
0
Order By: Relevance
“…The products of the strawberry AQP-encoding genes FaPIP1;1 and FaNIP1;1 both appear to be involved in the transport of water into the fruit [10,11]. A number of authors have reported that plant AQPs respond to external stress, triggering physiological adjustments which act to maintain the plant’s hydration status [12,13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The products of the strawberry AQP-encoding genes FaPIP1;1 and FaNIP1;1 both appear to be involved in the transport of water into the fruit [10,11]. A number of authors have reported that plant AQPs respond to external stress, triggering physiological adjustments which act to maintain the plant’s hydration status [12,13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, E. salsugineum, with a small genome, is quite tolerant to salt, drought and low temperature stresses, being considered to be a halophyte model plant for investigating the mechanism of plant resistance to stress (Zhu, 2001;Inan et al, 2004). The E. salsugineum AQPs like TsTIP1;2, TsMIP6 and TsPIP1;1 have been found to play an important role in plant response to abiotic stress (Wang et al, 2014;Li et al, 2018). The E. salsugineum genome was sequenced in 2012 and at the chromosome level and scaffold level, respectively (Wu et al, 2012;Yang et al, 2013), promoting the bioinformatics analysis of whole aquaporin family.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, E. salsugineum has a small genome, and also tolerant to salt, drought and low temperature stress, thus it is considered to be a halophyte model plant for investigating the mechanism of plant resistance to stress (Zhu, 2001;Inan et al, 2004). The E. salsugineum AQPs like TsTIP1;2, TsMIP6 and TsPIP1;1 have been found to play an important role in plant response to abiotic stress (Wang et al, 2014;Sun et al, 2015;Li et al, 2018). Since the E. salsugineum genome was sequenced in and 2013 at the chromosome level and scaffold level respectively (Wu et al, 2012;Yang et al, 2013), promoting the bioinformatics analysis of whole aquaporin family.…”
Section: Introductionmentioning
confidence: 99%